mGluR1α expression in the hippocampus, subiculum, entorhinal cortex and superior temporal gyrus in Alzheimer’s disease - J.H.Y. Yeung; T.H. Palpagama; C. Turner; H.J. Waldvogel; R.L.M. Faull; A. Kwakowsky (IBRO Neuroscience Reports, 2022)
Glutamate is the main excitatory neurotransmitter in the central nervous system, responsible for a plethora of cellular processes including memory formation and higher cerebral function and has been implicated in various neurological disease states. Alzheimer’s disease (AD) is the leading neurodegenerative disorder worldwide and is characterized by significant cell loss and glutamatergic dysfunction. While there has been a focus on ionotropic glutamatergic receptors few studies have attempted to elucidate the pathological changes of metabotropic glutamate receptors (mGluRs) in AD. mGluRs are G-protein coupled receptors which have a wide-ranging functionality, including the regulation of neuronal injury and survival. In particular, the group I mGluRs (mGluR1 and mGluR5) are associated with ionotropic receptor activation and upregulation with resultant glutamate release in normal neuronal functioning. The mGluR subtype 1 splice variant a (mGluR1α) is the longest variant of the mGluR1 receptor, is localized to dendritic processes and is mainly plasma membrane-bound. Activation of mGluR1a has been shown to result in increased constitutive activity of ionotropic receptors, although its role in neurodegenerative and other neurological diseases is controversial, with some animal studies demonstrating potential neuroprotective properties in excito- and neurotoxic environments. In this study, the expression of mGluR1a within normal and AD human hippocampal tissue was quantified using immunohistochemistry. We found a significantly reduced expression of mGluR1α within the stratum pyramidale and radiatum of the CA1subregion, subiculum, and entorhinal cortex. This downregulation could result in potential dysregulation of the glutamatergic system with consequences on AD progression by promoting excitotoxicity, but alternatively may also be a neuroprotective mechanism to prevent mGluR1α associated excitotoxic effects. In summary, more research is required to understand the role and possible consequences of mGluR1α downregulation in the human AD hippocampus, subiculum and entorhinal cortex and its potential as a therapeutic target.